Retinal Dysfunction in Patients with Congenital Fibrosis of the Extraocular Muscles Type 2. (2nd April 2016) - Khan, Arif O.; Almutlaq, Mohammed; Oystreck, Darren T.; Engle, Elizabeth C.; Abu-Amero, Khaled; Bosley, Thomas
Abstract: Introduction : Congenital fibrosis of the extraocular muscles type 2 (CFEOM2) is a distinct non-syndromic form of congenital incomitant strabismus secondary to orbital dysinnervation from recessive mutations in the gene PHOX2A . The phenotype includes bilateral ptosis, very large angle exotropia, ophthalmoplegia, and poorly-reactive pupils. Other than amblyopia, afferent visual dysfunction has not been considered part of CFEOM2; however, we have repeatedly observed non-amblyopic subnormal vision in affected patients. The purpose of this study was to document this recurrent feature of the phenotype. Methods : A retrospective case series (2002–2012). Results : Eighteen patients (four families) were identified; all affected individuals had confirmed homozygous recessive PHOX2A mutations except one individual for whom genetic testing was not done because of multiple genetically confirmed family members. Age at assessment ranged from 5–62 years old (median 10 years old). All patients had decreased best-corrected visual acuity not completely explainable by amblyopia in both the preferred and non-preferred eye. In those patients who had further ancillary testing, visual fields (five patients) and electroretinography (10 patients) confirmed abnormalities not ascribable to amblyopia. Conclusions : In addition to a distinct form of congenital incomitant strabismus, the phenotype of CFEOM2 includes subnormal vision consistent with retinal dysfunction. This could be the direct result of PHOX2A mutations or a secondary effect of orbital dysinnervation.